Extensor Tendon Entrapment on Computed Tomography Imaging of Distal Radius Fractures - Nigh, Evan D.; Emerson, Christopher P.; To, David; Barnhill, Spencer; Rizzo, Michael G.; Nguyen, Duc M.; Ugarte, Ane; Muñera, Felipe; Greif, Dylan N.; Jose, Jean; Dodds, Seth D. (Journal of Wrist Surgery, 2020)
Objective To examine the association between distal radius fractures and tendon entrapment identified on computed tomography (CT) imaging.Patients and Methods After Institutional Review Board approval, we retrospectively reviewed distal radius fractures that underwent CT imaging from an electronic database between January 2006 to February 2018 at a single level 1 hospital trauma center. We categorized all distal radial fractures according to the AO-OTA (AO Foundation/Orthopaedic Trauma Association) classification. Distal upper extremity tendons were assessed for entrapment. Fisher's exact test was used for statistical analysis with significance at p < 0.05.Results A total of 183 distal radius fractures were identified in 179 patients. A total of 16 fractures (13 males and 3 females) were associated with tendon entrapment. Mechanism of injury included falls (n = 7), motor vehicle accidents (n = 6), dog bites (n = 2), and gunshot wound (n = 1). Entrapped tendons were limited to the extensor compartment and included the extensor pollicis longus (EPL; n = 11), extensor pollicis brevis (n = 1), extensor carpi ulnaris (n = 1), extensor carpi radialis longus (n = 1), and extensor digitorum communis (n = 2). The most commonly associated AO-OTA fracture pattern with tendon entrapment was complete articular radial fractures (2R3C; 69%), eight of which were simple articular with metaphyseal multifragmentary fractures (2R3C2). Of the distal radius fractures, 81% were associated with additional ulnar fractures of varying severity and displacement.Conclusion Approximately 8.7% of distal radius fractures were retrospectively identified to have tendon entrapment compared with a previously reported incidence of 1.3%. Wrist surgeons and radiologists should have higher suspicion for tendon entrapment and carefully review preoperative CT imaging for tendon entrapment in distal radius fractures especially if there is an intra-articular, multifragmentary injury pattern. Wrist surgeons and radiologists should also have increased suspicion for EPL tendon entrapments given its high incidence in association with distal radius fractures.Level of Evidence This is a Level III, retrospective cross-sectional study.
Keywords: distal radius fracture; tendon entrapment; computed tomography; AO-OTA classification